Induction of tolerance to bacterial wilt in hybrids of tomatoes by application of gibberellin - Rodrigues, Fabrício; Nunes, Ana Carolina Pacheco; Carvalho, Daniel Diego Costa; Ribeiro, Mylla Crysthyan (Revista de Ciências Agroveterinárias, 2018)
The bacterial wilt (Ralstonia solanacearum) is a serious problem to produce Solanaceae plants in several Brazilian regions, mainly under protected environments. The gibberellin (GA3) is a hormone that has its proven efficiency to increase several traits in tomato plants, however, there is no study about the potential of this hormone for the induction of disease tolerance. Thus, the objective of the work was to study the effect of the application of gibberellin to increase tolerance in tomato hybrids to bacterial wilt. The experimental design was a randomized block design, in a factorial scheme 8 x 5 (hybrids and application times), with three replications. The variables of plant height, number of flowers, fresh shoot mass, transverse diameter of fruits, number of fruits and fruit weight were studied after 120 days of sowed. It was verified that there is significant difference for all variables studied and for the sources of variation. The gibberellin can induce increased tolerance in tomato plants to bacterial wilt, however, the time of application is dependent on the hybrid and the desired variable to obtain the best performance. The application on the 24th day, after planting, was the one that presented the high gains in the different hybrids and variables, followed by the 32nd day.